Kinetic Modeling of Reactive Absorption of Carbon Dioxide in a Spray Dryer. Issue 3 (7th February 2013) - Kavoshi, L.; Hatamipour, M. S.; Rahimi, A.
Abstract A semi‐empirical kinetic correlation was obtained through a shrinking core model assumption for reactive absorption of CO2 with NaOH solution by applying response surface method analogy in a laboratory‐scale spray‐dryer absorber. The effect of approach temperature, absorbent concentration, nozzle diameter, and L/G ratio on the kinetic coefficient was studied and the optimum operating conditions to reach the maximum absorption were determined.